Iraq and the future of Arabs - Al-Sheikh, Manal Salem (Arab Journal for Sciences and Research Publishing, 2019)
This study aimed to reveal the reality of what was happening in Iraq at the period of the Second Gulf War 1990-1991, of instability and the gray scene of the Arab landscape. And the impact of datums and events at the Iraqi territory on the Iraqi minorities and the other Arab countries, and how the future of these countries will be after the American penetration in Iraq, all the relevant literature has been surveyed to success the goal of the study. The researcher presented a neutral proposal to the current considerations and developments in the Arab region and he suggested a vision to override the Iraqi crisis with minimal losses.
Keywords: Iraq; the future of the Arabs; instability; modernity